Hubungan Paparan Informasi dengan Pengetahuan Pencegahan Kekerasan Seksual di SMK NU Muara Padang Kabupaten Banyuasin - Anggun Kesuma; Rotua Lenawati Tindaon; Yona Wia Sartika (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2026)
Background: Sexual violence remains a serious global and national issue. The World Health Organization reports that approximately one in three women worldwide have experienced physical or sexual violence. In Indonesia, 445,502 cases of violence against women were recorded in 2024, with 26.94% classified as sexual violence. Adolescents are a vulnerable group, highlighting the need for prevention efforts through improved knowledge influenced by information exposure. Method: This study used a quantitative design with a cross-sectional approach. The sample consisted of 141 respondents selected using proportional stratified random sampling technique. Data were collected using validated and reliable questionnaires and analyzed using univariate and bivariate analysis with the Chi-square test. Results: The majority of respondents had high knowledge (84.4%) and high information exposure (53.9%). There was a significant relationship between information exposure and knowledge of sexual violence prevention (p = 0.042; PR = 1.180). Additionally, father’s education (p = 0.000; PR = 1.361) and mother’s education (p = 0.001; PR = 1.299) were significantly associated with knowledge. Meanwhile, parenting style (p = 0.322), family income (p = 0.382), and living status with parents (p = 1.000) were not significantly related. Conclusion: Information exposure and parental education are associated with knowledge of sexual violence prevention. Therefore, increasing access to educational information through digital media, schools, and families is necessary to improve adolescents' knowledge. Keywords: Adolescents, Education, Information Exposure, Knowledge, Sexual Violence Prevention